Melanosternarchus amaru, a new genus and species of electric ghost knifefish (Gymnotiformes: Apteronotidae) from the Amazon Basin - Bernt, Maxwell J.; Crampton, William G. R.; Orfinger, Alexander B.; Albert, James S. (Zootaxa, 2018)
We describe Melanosternarchus amaru as a new genus and species of Apteronotidae from the deep channels of blackwater and clearwater tributaries of the Amazon River in Brazil and Peru. The new species superficially resembles members of the widespread “Apteronotus” bonapartii species group, from which it can be readily distinguished by expanded bones of the infraorbital laterosensory canal. It can further be distinguished from all other apteronotids by a unique combination of characters: reduced premaxillary dentition, a large gape, and an absence of scales from the entire dorsum. A molecular phylogenetic analysis using three mitochondrial loci and one nuclear locus (~3000 bp) places this genus as sister to Compsaraia, and these two genera together as a clade sister to Pariosternarchus; all nodes with strong statistical support. The clade formed by these three genera includes five species, four of which are restricted to the Amazon basin. The apparent habitat preference of the new species for low-conductivity blackwater and clearwater rivers has not been reported in other apteronotid species.